COMMUNISM, VALUE NEUTRALITY AND MONETARY NEUTRALITY - LUO, Yinghao (Theoretical and Practical Research in Economic Fields; Vol 8 No 2 (2017): TPREF, Volume VIII, Issue 2(16), Winter 2017DO - 10.14505/tpref.v8.2(16).07, 2017)
One of the most puzzling aspects about the functioning of the floating exchange rate regime of the 1980s has been that huge swings in exchange rate have had only muted effects on anything real. To understand this phenomenon, we study the relationship between communism and value neutrality and monetary neutrality. We find that the symmetry of communism is bound to lead to value neutrality. In the case of value neutrality, the economic man will certainly accept monetary neutrality. If money is neutral in the long run then even if purchasing power parity (PPP) is not valid in the short-run it will valid over the long run. However, without considering the time factor, communism is a kind of symmetry that is almost impossible to achieve. While considering the time factor, the symmetry of communism can be achieved in theory!